STUDI LITERATUR PEMANFAATAN TEKNOLOGI DIGITAL DALAM PENDIDI-KAN 4.0: INOVASI, TANTANGAN, DAN IMPLIKASI ABAD 21 - Najwa Asy Syifa El Khair Siagian; Septina Kristin Pane; Fatma Tresno Ingtyas; Laurena Ginting (STKIP Subang, 2026)
The digital transformation in the era of the Fourth Industrial Revolution presents both opportunities and challenges for the education sector. On one hand, digital technology enhances the effectiveness, flexibility, and quality of learning; on the other hand, disparities persist in infrastructure, teachers’ digital literacy, and the risks associated with excessive technology use. This study aims to analyze the role, innovations, challenges, and implications of digital technology within the framework of Education 4.0 and 21st-century learning. The research employed a descriptive qualitative method through a literature review of 15 SINTA-accredited journal articles. The results indicate that digital learning media—such as e-learning platforms, interactive videos, simulations, and project-based learning—support the development of 21st-century competencies, including critical thinking, creativity, communication, and collaboration. However, the study also identifies several challenges, such as limited facilities, unequal internet access, and teachers’ readiness to adopt digital tools. The findings emphasize that strategies for integrating technology must be systematically, innovatively, and sustainably designed to enable digital technology to act as a catalyst for improving education quality. Therefore, this study highlights the importance of resource preparedness, continuous teacher professional development, and adaptive educational policies to strengthen the implementation of Education 4.0 in Indonesia.